Patient voice and health education for familial hypercholesterolaemia. (March 2022) - McIntosh, Scott; Coykendall, Cameron; Lin, Yifei Sylvia; Caufield, Matthew; Muller, Joe; Rowe, Tina; Block, Robert C
Objective: Familial hypercholesterolaemia (FH), an autosomal dominant disorder causing elevated low-density lipoprotein (LDL) cholesterol from birth resulting in premature cardiovascular disease, is only diagnosed in 10% of affected patients. This study involved partnering with patients with FH and with primary care providers (PCPs) to understand health priorities and translate them into hypotheses for future research and enhancement of health practices via electronic health records (EHRs). The goal was to strengthen genetic health education for clinicians and for patients and their families, including improved diagnosis, knowledge and treatment. Perceptions regarding genetic health education and healthcare related to FH facilitated by the use of an EHR for diagnosis and treatment have not been studied. Design: Mixed-methods exploratory qualitative research and surveys. Setting: Qualitative research included five focus groups, 34 semi-structured key informant interviews and open-ended survey items with patients and PCPs at a large medical centre in Western New York. Method: Data were thematically coded to identify themes as formative work for the improvement of relevant EHR features, diagnosis, treatment and genetic health education via information sharing between clinicians and patients. Results: Themes included genetic health knowledge; the importance of being diagnosed; communication between patients, family members and medical professionals; outreach via patients' own advocacy; and treatment, technology, motivation, trust, outside resources (for further genetic health education and support) and awareness of effective treatments. Conclusion: Patients and clinicians can contribute to the development of EHR support for the genetic health education of patients and their families, and for improved diagnosis and treatment of FH. Using their ideas in the development of effective strategies could improve the currently low rate of FH diagnosis and cascade screening (for family members), as well as enhance physician and patient genetic health knowledge and self-empowerment.